Pathology and Biology of Human Germ Cell Tumors - Nogales, Francisco F.; Jimenez, Rafael E. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides, for the first time, a detailed, up-to-date, holistic approach to the pathology and biology of germ cell tumors. The main focus is the complex histopathology of these tumors, but special considerations are also given to their morphologic variations in relation to age, gender and organ. Critical updates are provided on terminology and classification; the discussion of biology and pathogenesis includes references to many molecular genetic and immunohistochemical findings from recent stem cell research. Individual chapters are devoted to germ cell tumors at different anatomic locations, including not only the ovaries and testes but also the mediastinum and central nervous system, and pediatric tumors. All of the contributing authors are opinion leaders from universities of excellence in Europe and the United States. This monograph will be of wide interest to practitioners and researchers in many fields of medicine, including pathology, gynecology, urology, and pediatrics, as well as stem cell scientists.
Keywords: Medicine.; Gynecology.; Internal medicine.; Pathology.; Pediatrics.; Urology.; elektronické knihy; electronic books